T-shirts for dialogue (Journal of Parents and Teachers, 2014)
A simple shirt can become the ideal ally for a school's educational project. That same has been demonstrated at Duke University in North Carolina when a group of students stamped on their T-shirts a motto to curb homophobia. Thus, the article proposes to create in colleges and universities the so-called "t-shirts for dialogue".
Keywords: T-shirt; slogan; education; dialogue.